Neo-Sufism as a Social Da'wah Paradigm: Addressing Challenges and Transforming Spirituality in Modern Indonesia - Budi Rahman Hakim (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
In contemporary Indonesia, Neo-Sufism has emerged as a significant paradigm for Islamic social da'wah, particularly in response to growing spiritual disorientation, religious radicalism, and socio-cultural fragmentation in urban contexts. This research explores how institutionalized Sufi orders, especially those rooted in traditional tarekat such as TQN is redefining their spiritual missions through transformative, socially-engaged practices. Using a qualitative library-based methodology, the study analyzes primary and secondary texts to trace how core Sufi values—such as ikhlas (sincerity), sabr (patience), and zuhd (asceticism)—are applied within modern da'wah strategies. Rather than functioning as apolitical or inward-facing traditions, these Sufi orders have implemented socially responsive initiatives including pesantren-based empowerment, Sufi clinics, and ethical microeconomics. The findings challenge stereotypes of Sufism as detached from social realities and instead position Neo-Sufism as a framework for moral reform and community development. This rearticulation of Sufism not only addresses urban spiritual crises but also contributes a sustainable and values-based model of religious engagement. To ensure continued relevance, the study recommends strengthening urban Sufi literacy and institutional collaboration among tarekat networks.